La economía española en la Unión Europea de los 25 - Anchuelo Crego, Álvaro; Pérez Garrido, Marta (Papeles del Este, 2007)
The Spanish economy has performed well during the last decade, growing faster than the other large economies of the EU-15. However, some qualitative indicators show that the kind of growth achieved could be unsustainable. The new members of the EU already have values in some of those indicators, such as the technological content of the industrial production and exports, or the FDI received, that are similar or even better than the Spanish ones. The problems could be solved through improvements in the technologies and the human capital. But Spain still has, in these aspects, a situation that is far worse than in the more advanced members of the EU, and not much better than in the new eastern members.